ROLE OF CYTOTOXIC T LYMPHOCYTE IN ADENOVIRUS INFECTION - Yasameen Waleed AL-Abedi; Ali Abdulhussein Alsaeedi; Alaa Abdalhadi Halboti (Journal of Medical Genetics and Clinical Biology, 2024)
The successful development of adenovirus vectors for vaccines and gene therapy will require a better understanding of the host immune response. Using the ELISPOT assay to measure IFN-g-secreting CD8þ cells, we identify immunodominant epitopes of the adenovirus hexon and DNA-binding protein in BALB/c and C57BL/6 mice. The T-cell response to the intramuscular administration of adenovirus serotype 5 peaks within a few weeks and gradually declines but is still detectable after 12 weeks. A second administration did not substantially increase the number of reactive T cells. The CD8þ T-cell response was also similar between wild type and E1-deleted adenovirus. When B-cell-deficient mice were injected with adenovirus encoding the gene for secreted alkaline phosphatase, sera phosphatase activity was reduced more quickly in mice pre-exposed to adenovirus. These results add to the evidence that cell-mediated immunity is a substantial barrier to therapeutic adenoviral vectors and provide more quantitative tools to measure cellular immune responses to adenovirus.